AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DI NAGARI SICINCIN KECAMATAN 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Fitria, Nita (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
This paper aims to study the accountability of Nagari financial management in Sicincin, 2X11 Enam Lingkung, Padang Pariaman regency in 2017. This type of research is Field Research with descriptive method. Data collection techniques in this research used interviews and collection of documents. The results showed that the government of 2X11 Enam Lingkung Nagari Sicincin of Padang Pariaman Regency had applied the principles of accountability in the management of Nagari finance in 2017. In general, accountability had begun to be implemented. However, there are still some indicators of accountability criteria that have not been implemented by the government of Nagari Sicincin.